Assessment of the Quality of Life in Patients with Bronchial Asthma and Obesity - Kuchkarova Shakhnoza (Genius Journals, 2023)
The confluence of bronchial asthma and obesity represents a complex interplay that significantly influences the quality of life for affected individuals. This article explores the multifaceted challenges in diagnosing and managing these intertwined health conditions and assesses their collective impact on well-being. The intersection of bronchial asthma and obesity introduces overlapping symptoms, requiring careful differential diagnosis. Optimizing medication efficacy becomes paramount, considering the altered physiology in individuals with both conditions. Lifestyle modifications, including exercise and dietary changes, demand a nuanced approach that addresses respiratory and weight-related aspects collaboratively. Patient adherence, education, and mental health considerations further contribute to the intricacies of care. As this dual health burden continues to gain recognition, ongoing research endeavors are crucial to bridge evidence gaps and inform best practices. A comprehensive, patient-centered approach is imperative, involving healthcare professionals, researchers, and individuals, to navigate the complexities of bronchial asthma with obesity and enhance overall wellbeing.
Keywords: Obesity; bronchial asthma; life quality